Sistem Pendukung Keputusan Seleksi Calon Karyawan Menggunakan Penerapan Metode PROMETHEE II - Luthfiah, Eva; Muslih, Muhamad (STIKOM Tunas Bangsa Pematangsiantar, 2022)
This company has a very good quality of imported foreign and domestic products, PT longvin's staff has played an important role in producing excellent quality products, so the company must have a fairly good staff, which can be carried out according to this procedure set by the company. appears in the selection or selection of candidates by the company, because the selection process may not meet the company's level of demand for certain positions, it does not function properly so that the results obtained are inaccurate and not on target. This study aims to determine the PROMETHEE approach that is implemented in a decision support system to determine prospective employee analysis at the PT, this study was conducted in order to obtain the right prospective employee analysis of PT LONGVIN INDONESIA, As expected by HRD and the company using the PROMETHEE II approach, the data collected through interviews with HRD and in accordance with the standards set by the company. The evaluation criteria used are 4: (k1) age, (K2) education, (K3) ability, (K4) domicile and evaluation of alternative candidates for employees as many as 5 people: (P1 ) Selvyana, (P2) Fitni Nugraha, (P3). From this research at PT. Longvin Indonesia, we get the results of the analysis that the PROMETHEE II method can be used to select prospective employees for analysis. of the 3 candidates that have been selected by the company with the alternative fitni nugraha (NET FLOW 0.8) which has the first rank set to be the first alternative, selvyana and has the result (net flow -0.5) as the second alternative. In the 3rd place there is Nenden Najir (NET FLOW -0.4), of the 3 candidates selected by the company, only 3 candidates are taken from the first rank. The application of this method has been tested well at PT Longvinn Indonesia, in order to make it easier to determine the best employees as expected by the company.decision support, PROMETHEE method, alternatives, criteria, PT LONGVIN INDONESIA